2006
DOI: 10.1038/nature05264
|View full text |Cite
|
Sign up to set email alerts
|

Haemagglutinin mutations responsible for the binding of H5N1 influenza A viruses to human-type receptors

Abstract: H5N1 influenza A viruses have spread to numerous countries in Asia, Europe and Africa, infecting not only large numbers of poultry, but also an increasing number of humans, often with lethal effects. Human and avian influenza A viruses differ in their recognition of host cell receptors: the former preferentially recognize receptors with saccharides terminating in sialic acid-alpha2,6-galactose (SAalpha2,6Gal), whereas the latter prefer those ending in SAalpha2,3Gal (refs 3-6). A conversion from SAalpha2,3Gal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
520
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(547 citation statements)
references
References 24 publications
15
520
1
4
Order By: Relevance
“…H1, H2 and H3 (Stevens et al, 2004;Tumpey et al, 2007). However, the H5 HA structural adaptation to the human receptor binding requires further defi nition (Yamada et al, 2006). It has been shown that experimental changes at position 226 and 228 (H3 numbering) in H5 resulted in the recognition of humantype receptors (Stevens et al, 2006).…”
Section: Structural Basis For Receptor-binding Changesmentioning
confidence: 99%
“…H1, H2 and H3 (Stevens et al, 2004;Tumpey et al, 2007). However, the H5 HA structural adaptation to the human receptor binding requires further defi nition (Yamada et al, 2006). It has been shown that experimental changes at position 226 and 228 (H3 numbering) in H5 resulted in the recognition of humantype receptors (Stevens et al, 2006).…”
Section: Structural Basis For Receptor-binding Changesmentioning
confidence: 99%
“…This indicated that they were highly pathogenic (Senne, et al, 1996). None of them carried the mutations 129AV, 134AV, 182AK, 192AR, 222AL, 223AN or 224AS (H5 numbering) in the HA gene, which could render the virus binding to human SAa2,6Gal receptors and facilitate the virus replicate efficiently in humans (Auewarakul et al, 2007;Stevens, et al, 2006;Yamada et al, 2006).…”
mentioning
confidence: 99%
“…The first synthetic replikins pan-influenza vaccine was successful against H5N1; it also blocked virus excretion, providing for the first time the potential to block the development of H5N1 reservoirs (Table II and Figure 3a) is here shown to occur in advance of and during the pandemic. This change is concomitant with changes from neutral to acidic conformation assisting fusion of the virus with the host membrane during virus entry (27)(28)(29)(30). The actual visualization of Replikins, with the ability to count them, supports the reality and practical clinical relevance of Replikin structures.…”
Section: Pan-influenza Vaccinesmentioning
confidence: 93%
“…The central role of the sialic acid receptor for influenza virus entry into host cells was demonstrated a) in 1959 by the authors by blocking the virus entry into brain cells by sialic acid conjugates from brain gangliosides (25), and b) by the release of similar sialic acid conjugate decoys (sialoresponsins) by the chorioallantoic membrane of the chick egg under influenza attack (26). The molecular definition of the reaction between the hemagglutinin unit and the sialic acid receptor pocket of the host membrane was recently demonstrated (27)(28)(29)(30).…”
Section: Pan-influenza Vaccinesmentioning
confidence: 99%